2011
DOI: 10.1364/oe.19.007468
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable hybrid diffractive/refractive achromatic lens

Abstract: We demonstrate a variable focal length achromatic lens that consists of a flat liquid crystal diffractive lens and a pressure-controlled fluidic refractive lens. The diffractive lens is composed of a flat binary Fresnel zone structure and a thin liquid crystal layer, producing high efficiency and millisecond switching times while applying a low ac voltage input. The focusing power of the diffractive lens is adjusted by electrically modifying the sub-zones and re-establishing phase wrapping points. The refracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…15 Recent publications show that this concept is still being manipulated for achromatization. 16,17 In the refractive case, dispersion caused by the material dominates, whereas, the structure of the element controls the diffractive dispersion. Given these two very different causes, diffraction and refraction cannot be balanced in a single element.…”
Section: Refractive and Diffractive Opticsmentioning
confidence: 99%
“…15 Recent publications show that this concept is still being manipulated for achromatization. 16,17 In the refractive case, dispersion caused by the material dominates, whereas, the structure of the element controls the diffractive dispersion. Given these two very different causes, diffraction and refraction cannot be balanced in a single element.…”
Section: Refractive and Diffractive Opticsmentioning
confidence: 99%
“…The extra alignment makes these lenses expensive and bulky. Hybrid refractive-diffractive lenses perform slightly better, but their complexity is even higher 12 13 14 . Such designs that work for more than three wavelengths are seldom studied.…”
mentioning
confidence: 99%
“…When fluidic lens 1 is applied to longer focal lengths the accuracy of fluidic lens 2 decreases. Previous work has shown that at 50 μL increments we were able to achieve 0.02%-0.88% accuracy on the radius of curvature for radii of curvature between 20 and 100 mm [17]. Relative to focal length, this radius-of-curvature range is equivalent to a focal length range between 60 and 300 mm; this is shown in Fig.…”
Section: Fabrication and Testing Of The Fluidic Lens Designsmentioning
confidence: 69%
“…Various fluidic lens designs have produced rotationally symmetric lenses as well as cylinder lenses [16]. Further advanced technologies have coupled fluidic lenses with variable diffractive lenses, producing a hybrid achromat design [17]. As fluid lens technology has matured, multilens zoom systems and aberration correction systems have been analyzed [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%